2005
DOI: 10.1017/s0266467405002440
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in the understorey shrub genus Psychotria in central Amazonia: effects of distance and topography

Abstract: We evaluated the effects of topography on the distribution of understorey herbs, shrubs and small trees of the pantropical genus Psychotria (Rubiaceae) in a 10000-ha rain-forest reserve in central Amazonia. As plots were long and thin, and followed altitudinal isoclines, we were able to avoid the trade off between plot size and precision of measurement of topographical variables. The minimum distance between plots (1 km) was sufficient to avoid spatial autocorrelation in topographical variables. However, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 56 publications
3
57
1
3
Order By: Relevance
“…This study adds to the growing body of evidence suggesting that the natural heterogeneity found in a tropical forest can affect the local composition of animal and plant communities [17,21,[38][39][40][41][42][43][44][45][46][47][48]. Although we found that none of the variables analyzed were significantly associated with the number of bird species (richness) and individuals (abundance) recorded either on mist-nets or acoustic surveys, we found significant relationships between at least three parameters (elevation, distance to the nearest stream, and depth of the leaf litter) and bird species composition.…”
Section: Discussionmentioning
confidence: 92%
“…This study adds to the growing body of evidence suggesting that the natural heterogeneity found in a tropical forest can affect the local composition of animal and plant communities [17,21,[38][39][40][41][42][43][44][45][46][47][48]. Although we found that none of the variables analyzed were significantly associated with the number of bird species (richness) and individuals (abundance) recorded either on mist-nets or acoustic surveys, we found significant relationships between at least three parameters (elevation, distance to the nearest stream, and depth of the leaf litter) and bird species composition.…”
Section: Discussionmentioning
confidence: 92%
“…Das famílias com maior riqueza de espécies entre os arbustos e subarbustos, Rubiaceae é característica da vegetação do sub-bosque em muitas florestas (Kinupp & Magnusson 2005). Nota-se que Psychotria, táxon citado por Joly et al (1991) como freqüente no estrato arbustivo da floresta ombrófila costeira, tem elevada riqueza de espécies nas florestas montanas mais úmidas como a área de estudo e São Vicente Férrer (Ferraz 2002) e poucas espécies nas florestas montanas mais secas (Rodal & Nascimento 2002).…”
Section: Discussionunclassified
“…O gênero Psychotria foi comum no estrato regenerativo de todos os ambientes estudados, representado pelos maiores valores de densidade. Este gênero é caracterizado por espécies mais exigentes em condições ambientais, como a menor incidência de luz e maior umidade no solo, compreendendo significativa proporção da vegetação de sub-bosque em muitas florestas tropicais (KINUPP; MAGNUSSON, 2005), sendo que a tendência é o incremento do número de espécies arbóreo-arbustivas no transcorrer da regeneração natural (PESSOA et al, 1997). Essa substituição, segundo Nykvist (1996), ocorre em função das mudanças das condições abióticas, conferindo maior habilidade competitiva às espécies mais exigentes, em detrimento das herbáceas e pioneiras.…”
Section: Resultsunclassified